Duc de Broglie : a political study - Cordilico, Ronald, 1942- (My University, 1966)
Contents include: the early years, Duc de Broglie - Doctrinaire, opposition to ultra-royalism, the revolution of 1830, the foreign ministry of the Duc de Broglie, and growing conservatism.
120, [4] leaves ; 29 cm.
Keywords: Broglie, Achille Charles Leonce Victor, duc de, 1785-1870.